Vitamin K status, all-cause mortality, and cardiovascular disease in adults with chronic kidney disease: the Chronic Renal Insufficiency Cohort. Issue 3 (12th November 2021) - Shea, M Kyla; Barger, Kathryn; Booth, Sarah L; Wang, Jifan; Feldman, Harold I; Townsend, Raymond R; Chen, Jing; Flack, John; He, Jiang; Jaar, Bernard G; Kansal, Mayank; Rosas, Sylvia E; et al.
ABSTRACT: Background: Vascular calcification contributes to cardiovascular disease (CVD) and mortality in individuals with chronic kidney disease (CKD). Vitamin K-dependent proteins function as calcification inhibitors in vascular tissue. Objectives: We sought to determine the association of vitamin K status with mortality and CVD events in adults with CKD. Methods: Plasma dephospho-uncarboxylated matrix gla protein ((dp)ucMGP), which increases when vitamin K status is low, and plasma phylloquinone (vitamin K1), which decreases when vitamin K status is low, were measured in 3066 Chronic Renal Insufficiency Cohort participants (median age = 61 y, 45% female, 41% non-Hispanic black, median estimated glomerular filtration rate [eGFR] = 41 mL/min/1.73m 2 ). The association of vitamin K status biomarkers with all-cause mortality and atherosclerotic-related CVD was determined using multivariable Cox proportional hazards regression. Results: There were 1122 deaths and 599 atherosclerotic CVD events over the median 12.8 follow-up years. All-cause mortality risk was 21–29% lower among participants with plasma (dp)ucMGP <450 pmol/L ( n = 2361) compared with those with plasma (dp)ucMGP ≥450 pmol/L (adjusted HRs [95% CIs]: <300 pmol/L = 0.71 [0.61, 0.83], 300–449 pmol/L = 0.77 [0.66, 0.90]) and 16–19% lower among participants with plasma phylloquinone ≥0.50 nmol/L ( n = 2421) compared to those with plasma phylloquinone <0.50 nmol/L (adjusted HRs: 0.50, 0.99 nmol/L = 0.84 [0.72, 0.99], ≥1.00 nmol/L = 0.81 [0.70, 0.95]). The risk of atherosclerotic CVD events did not significantly differ across plasma (dp)ucMGP or phylloquinone categories. Conclusions: Two biomarkers of vitamin K status were associated with a lower all-cause mortality risk but not atherosclerotic CVD events. Additional studies are needed to clarify the mechanism underlying this association and evaluate the impact of improving vitamin K status in people with CKD.